Interatrial conduction time is early marker of disturbed impulse propagation in adults with slightly elevated blood pressure - Djikić, Dijana; Mujović, Nebojša; Giga, Vojislav; Marinković, Milan; Trajković, Goran; Lazić, Snežana; Pavlović, Vedrana; Perić, Vladan; Simić, Dragan (Vojnosanitetski pregled, 2021)
Background/Aim. Interatrial conduction time is early marker of disturbed impulse propagation in adult with elevated blood pressure. The aim of our study was to evaluate significance of noninvasive echocardiographic marker of slow sinus impulse propagation (atrial conduction time) for the identification of persons with slightly elevated blood pressure and hypertension in adults. Methods. One hundred and forty nine adults with normal and elevated blood pressure were studied: 46 normotensive adults (group 1), 28 adults with elevated blood pressure and hypertension stage 1 (group 2) and 75 adults with hypertension stage 2 (group 3), based on the Joint National Committee 8 (JNC-8) hypertension guidelines. We studied P wave dispersion, reservoir function of the left atrium (LA), total emptying volume of the LA and total emptying fraction of the LA (LATEF). The atrial conduction time (ACT) was evaluated by the pulsed tissue Doppler, and expressed as interatrial and intraatrial conduction time. Results. The LATEF decreased progressively from the group 3 (64.8 ± 4.4%) to the group 2 (59.8 ± 5.2%) and the group 1 (55.6 ± 7.3%) (p < 0.001). The P wave dispersion (55.1 ± 9.8 ms vs. 46.8 ± 3.1 ms vs. 43.1 ± 2.6 ms; p < 0.01) and intra ACT were significantly prolonged only in the group 3 compared to the other groups (22.7 ± 11.0 ms vs. 8.4 ± 4.7ms vs. 5.6 ± 2.4 ms, respectively; p < 0.001). Inter ACT significantly increased from the group 1 to the group 2 and the group 3 (15.6 ± 3.9 ms vs. 24.6 ± 5.7 ms vs. 50.4 ± 20 ms, respectively; p < 0.05). Using a cut-off level of 19.5 ms, inter ACT could separate adults in the group 2 from the group 1 with a sensitivity of 85%, and specificity of 89% [area under receiver operating characteristic (ROC) curve 0.911]. Conclusion. Prolonged ACT estimated with the tissue Doppler may be useful for identification persons with slighty elevated blood pressure, and hypertension stage 1.